Gender and the expansion of non-traditional agricultural exports in Uganda - Ann Whitehead; Jessica Vivian; Matthew Lockwood; Deborah Kasente (United Nations Research Institute for Social Development (UNRISD), 2000)
Agricultural policy is at the heart of poverty-focused macroeconomic policy in Uganda. Women are central to agricultural production in the country, and agriculture is critically important to women's well-being. It is therefore crucial that Ugandan agricultural policy become more gender-aware, after having long been 'gender-blind'. The research on which this paper reports sought to contribute to building national capacity for gender analysis in Uganda. The promotion of non-traditional agricultural exports (NTAE), one of the keystones of current macroeconomic policy in Uganda, was the subject of field study. Increasing agricultural production is crucial for the country's development, and NTAE promotion is now considered an important agricultural intensification strategy, given the demonstrated risks of over-reliance on world markets for the traditional cash cropscoffee, tea and cotton. But the implications of gender structures for the success of the NTAE promotion strategy, and the implications of this policy shift for gender relations and women's well-being, are not well understood. The research thus sought to provide information that would contribute to 'engendering' agricultural policy. It addressed two broad sets of questions concerning the efficiency and equity of the NTAE policy. First, how would current gender relations, including the gender division of labour and control over resources, affect the NTAE promotion strategy? What factors would be necessary for the desired supply response to policy initiatives to materialize? Second, how would the NTAE strategy, as currently conceived, affect women's well-being and their standing in the household and in society? What would be required for the NTAE promotion strategy to not only contribute to aggregate production, but to do so without adversely affecting any groups in society? Besides reviewing the implications of recent data and research for these questions, the project also carried out participatory rural appraisal exercises and conducted two village surveys in order to address them. The paper begins with an overview of the analytical approach of the research and then provides information on the national context in Uganda, including the agricultural sector economic policy, and gender issues and public policy. It goes on to look at the rural sector in Uganda, including gender roles in agriculture. Macroeconomic policy in Uganda is then discussed, as is the potential for and the constraints on an agricultural export-led growth strategy. The findings of the field studies are then described, in particular the factors limiting productivity in the smallholder sector. The paper concludes by describing an 'ideal' NTAE strategy-one that would lead to agricultural intensification, with increased inputs (labour and non-labour) resulting in increased outputs. Production for own consumption would either remain at current levels, or the income from marketed crops would be sufficient to allow sufficient purchase of food. At this time, however, rural Uganda is not reflected in this scenario. Constraints on increased productivity exist both in terms of input-seasonal labour shortages, lack of access to inputs, lack of credit, lack of knowledge-and in terms of incentives-lack of confidence in markets and pricing, high marketing margins, large price swings resulting in non-ability to purchase food prior to the harvest season. Women's labour supply is very inelastic, and additional labour burdens on women are likely to be detrimental to the well-being of others in household. Thus increased NTAE production, in the absence of additional inputs, must come from crop switching or an increase in men's labour. The field research found some indication that the gender division of labour is less rigid than is often believed, and that men are prepared to participate more fully in all aspects of agricultural production if the incentives to do so are adequate. But will this imply that men will 'take over' women's crops to the detriment of women's position in the household? This remains an open question. Indeed, there is also some indication that women do not welcome the loss of autonomy resulting from more co-operative household production systems. The paper argues, however, that a more equitable distribution of labour burdens within smallholder households certainly has the potential to benefit women. What Uganda is likely to experience is a shift to a more integrated and co-operative household in the smallholder sector. Whether this will imply a loss of women's autonomy, or an increase in women's influence in a larger sphere, will depend on the characteristics of the particular men and women who are members of each household, as well as on the strength of government initiatives to further the educational, legal, and social status of women.
Keywords: 330